Impacts of Low-Cost Land Certification on Investment and Productivity - Holden, Stein T. (2012)
New land reforms are again high on the policy agenda and low-cost, pro-poor reforms are being tested in poor countries. This article assesses the investment and productivity impacts of the recent low-cost land certification implemented in the Tigray region of Ethiopia, using a unique household and farm-plot-level panel data set, with data from before and up to eight years after the reform. Alternative econometric methods were used to test and control for endogeneity of certification and for unobserved household heterogeneity. Significant positive impacts were found, including effects on the maintenance of soil conservation structures, investment in trees, and land productivity.